1991
DOI: 10.1055/s-2008-1071411
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Function Monitoring During the First Week of Life in Extremely Small Low Birthweight (ESLBW) Infants

Abstract: In order to evaluate the usefulness of early continuous EEG-monitoring in very preterm neonates, recordings with a Cerebral Function Monitor (CFM) were made prospectively in 31 ESLBW infants with birthweights below 901 grams, during their first week of life. The CFM background activity was, as expected from EEG studies, dominated by a suppression-burst pattern in 94% of the infants. Some infants had periods with more continuous EEG activity or suppression-burst changing into continuous. Patterns similar to sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
76
1
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(82 citation statements)
references
References 20 publications
3
76
1
2
Order By: Relevance
“…Cycles have been demonstrated in infants studied between 25 and 30 wk by the presence of alternating intervals of EEG discontinuity (23). The presence of cycles on aEEG has been reported as early as 26 wk (24,25). However, determination of cycles is difficult in extremely preterm neonates, since much of the aEEG tracing is discontinuous.…”
Section: Discussionmentioning
confidence: 99%
“…Cycles have been demonstrated in infants studied between 25 and 30 wk by the presence of alternating intervals of EEG discontinuity (23). The presence of cycles on aEEG has been reported as early as 26 wk (24,25). However, determination of cycles is difficult in extremely preterm neonates, since much of the aEEG tracing is discontinuous.…”
Section: Discussionmentioning
confidence: 99%
“…Electrographical seizure activity, often subclinical, is common and affects approximately 60-70 % of infants during the development of IVH 20,21,22 . Although many previous studies indicated that an association between PRSW and IVH, some studies showed that PRSW did not seem to be associated with IVH and were more often observed with white matter injury PVL 20 .…”
Section: Eeg and Intraventricular Hemorrhagementioning
confidence: 99%
“…17,18 Information on aEEG activity in extremely premature infants is still limited. 19 Therefore, the objective of this study was to prospectively investigate the development of aEEG activity in preterm infants Ͻ30 weeks of gestation. We have already published preliminary results on the occurrence of sleep-wake cycles in 38 preterm infants from this cohort.…”
mentioning
confidence: 99%
“…These 10-minute epochs were classified into 3 pattern categories as follows (Fig 1): • Sleep-wake cycles were defined as cyclical sinusoidal variations of both amplitude and continuity of aEEG activity with a minimum epoch duration of 20 minutes. 19,20 Bursts were defined as amplitudes Ͼ100 V. …”
mentioning
confidence: 99%